Extradisciplinary risk-taking: Design education as institutional critique. Issue 1 (1st April 2019) - Vodeb, Oliver
Risk in education in the creative field of communication design is usually seen in connection with creativity as subjective expression and innovation as desired impact. This article positions risk in relation to the political in design education. It puts forward the argument that a particular type of risk-taking in education can work towards shifting design from a position of a service-providing activity towards a more emancipated practice, which would not comply with the pressures of neoliberal capitalism. To counter the current state of compliance this article suggests a three-level model of extradisciplinary risk-taking as institutional critique. The case of Memefest and Design Futures is discussed. Theoretical analysis is combined with (auto) ethnography and qualitative research.